The efficiency of a supplementary old-age pension system: The case of Polish voluntary pension funds - Joanna Rutecka-Góra (e-Finanse: Financial Internet Quarterly, 2019)
The aim of this article is to evaluate the effectiveness of voluntary pension savings plans in Poland, based on the principles of operation and rates of return of voluntary pension funds (pol. Dobrowolne Fundusze Emerytalne, DFE). The selection of those funds from a whole range of solutions available in the 3rd pension pillar is due to the fact that only this type of voluntary pension saving plan provides complete and transparent information about the actual investment policy, the composition of pension investment portfolios, and the achieved rates of return. In order to evaluate the investment policies and the effectiveness of DFEs, the following research methods were used: a literature analysis, an analysis of financial data, and basic methods of investment efficiency assessment. The results of the evaluation lead to the conclusion that despite their adoption of similar investment strategies, the DFEs have achieved very different values of effectiveness. In the years 2013-2018, selected funds achieved higher than average rates of return, while others achieved returns that were no better than the interest rates of standard bank deposits.
Keywords: G23; J32; 330; old-age pension; pension system; supplementary pension; pension fund efficiency; pension savings